The Influence of Psychological Factors, Framing Effects, and Incidental Emotions on Young People's Stock Investment Decisions: A Case Study of Investment Education Content on TikTok - Salsabila Atiqah Zuhrah Hafizhah; Zaenal Arifin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of psychological factors (consisting of overconfidence, herding behavior, FOMO, emotions, and considering the past), framing effect, and incidental emotions on young people’s stock investment decisions, in the context of investment education content on the TikTok social media platform. The background of this study is based on the phenomenon of the rise of investment education content, especially in the stock sector on TikTok, and the increasing number of active young investors. The research approach uses a quantitative method. The sample consisted of 190 respondents who were active students of the Management Study Program, Islamic University of Indonesia, who invested in stock instruments. The results of the study showed that psychological factors had a significant influence on stock investment decisions. Meanwhile, when the psychological factors construct was tested, the results were only overconfidence and considering the past that influenced investment decisions. Meanwhile, herding behavior, FOMO, and emotions did not affect investment decisions. In addition, framing effect, incidental emotions, and investment education content were not proven to have a positive effect on investment decisions.